Stunning Australia - Probyn-Rapsey, Fiona (Humanimalia, 2013)
This article focuses on the Australian campaign to ban live exports of cattle to Indonesia in the wake of media exposure of cruel slaughterhouse practices there.  It examines Australian reactions to this footage and how Australian pride in the use of stunning technology (where cattle are stunned prior to bleeding) circulates as a point of national pride. What frames ‘our’ national pride is also a discourse of racialized shaming of Indonesian practices. The connections between stunning, insensibility and denial help to explain how and why Australian reactions took the shape that they did.